Experimental and theoretical insight into the transformation behaviors and risk assessment of Flutamide in UV/O3/PMS system. (15th November 2022) - Li, Xiaofan; Wang, Ning; Lv, Guochun; Zhang, Yonglei; Chen, Yanqi; Liu, Xiaoyu; Sun, Xiaomin; Zhu, Fanping
Abstract: Nowadays, the widespread existence and potential adverse effects of emerging micropollutants in waters have prompted the search for effective treatment methods. In this study, the feasibility of UV/O3 /PMS (peroxymonosulfate, HSO5 − ) method for the elimination of Flutamide (FLU) was comprehensively investigated, with focus on transformation behaviors and risk assessment. The results showed that the UV/O3 /PMS method has excellent oxidation capability to FLU with the elimination efficiency of 83.7% within 40 min. In addition, the radical (·OH and SO4 − ·) oxidation occupies greater advantages in the initiation reaction pathways of FLU compared to non-radical (O3 and 1 O2 ) oxidation. With the participation of H2 O2, H2 O, O2, and ·OH, eleven transformation products (TPs) are generated through hydroxylation, demethylation, and decomposition reactions. According to the risk assessment results, the toxicity of most TPs gradually decreased, but the residual developmental toxicity could not be ignored. Further, the environmental persistence of FLU was evaluated with respect to natural water and advanced oxidation processes. These findings could help to advance the fundamental understanding of emerging micropollutants in the aquatic environments, and provide a basis for their practical application in water treatment. Graphical abstract: Image 1 Highlights: The transformation mechanisms involved in UV/O3 /PMS system were elucidated. ·OH and SO4 − · are the major contributors to FLU degradation compared to O3 and 1 O2 . FLU degradation was caused by hydroxylation, demethylation, and decomposition paths. UV/O3 /PMS is a promising treatment method for O3 or UV-refractory micropollutants.